Towards a strategic transcultural model of leadership that enhances Koinonia in urban Southern Africa - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD (Science of Religion and Missiology))--University of Pretoria, 2007.